2021
DOI: 10.1002/jssc.202100360
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive multicomponent characterization and fingerprinting analysis of Lanqin Oral Liquid by ultra‐high‐performance liquid chromatography coupled with ion mobility‐quadrupole time‐of‐flight mass spectrometry

Abstract: Comprehensive characterization of the chemical constituents of Chinese patent medicine poses a great challenge due to the frustrating complexity resulting from superposition of multiple drugs. Lanqin Oral Liquid is a five‐component Chinese patent medicine widely applied to treat pharyngeal inflammation in clinic. Here, we streamline a universal three‐dimensional separation approach to efficiently identify the multicomponents from Lanqin Oral Liquid by ultra‐high‐performance liquid chromatography/ion mobility q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In order to improve the efficiency of metabolite characterization, it is necessary to develop the processing software containing a standard CCS value database . Wang et al identified many components in Lanqin Oral Liquid (a Chinese patent medicine) by UPLC-IM-QTOF-MS and automatic peak annotation driven by UNIFI software. The CCS data correlation global natural products molecular networking platform (GNPS) can further identify targeted or nontargeted compounds with a high throughput. …”
Section: Applications Of Im-ms For the Separation And Characterizatio...mentioning
confidence: 99%
“…In order to improve the efficiency of metabolite characterization, it is necessary to develop the processing software containing a standard CCS value database . Wang et al identified many components in Lanqin Oral Liquid (a Chinese patent medicine) by UPLC-IM-QTOF-MS and automatic peak annotation driven by UNIFI software. The CCS data correlation global natural products molecular networking platform (GNPS) can further identify targeted or nontargeted compounds with a high throughput. …”
Section: Applications Of Im-ms For the Separation And Characterizatio...mentioning
confidence: 99%
“…Therefore, it is most important to develop powerful analytical methods to identify or characterize the material basis of TCMFP. 6 This is of great significance to the modernization and globalization of TCM.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the chemical composition of traditional Chinese medicine formula preparations (TCMFP) may change in every link from active drug ingredient to finished product. Therefore, it is most important to develop powerful analytical methods to identify or characterize the material basis of TCMFP 6 . This is of great significance to the modernization and globalization of TCM.…”
Section: Introductionmentioning
confidence: 99%
“…Step 1: In order to determine the compound, the error range of the fragment ion peak should be less than 5 ppm [16]. Therefore, having high resolution and high sensitivity, UHPLC-quadrupole-TOF-MS (UHPLC-Q-TOF-MS) was used to analyze the composition of CNH ethanol extract to identify unknown compounds [17,18]. Step 2: Blood samples are analyzed at multiple time points using UHPLC-Q-TOF-MS to determine the CNH components in the plasma and compare them to the main components of CNH to confirm the absorbed components in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…hirsutissima. Z.Wei (CNH) solution, *5-Hydroxymethylfurfural (1), Gallocatechin (2), Daidzin (3), Genistein-7-o-β-d-apinoyl-(1→6)-O-β -d-glucopyranoside (4), Chickpea a7-o-β-d-glucopyranoside (5), Genistin (6), 3′-O-methylorobol (7), Butein (8), Ononin (9), Daidzein (10), Isoliquiritigenin (11), 8-methylretusin-7-O-β-D-glucopyranoside (12), Calycosin(13), Altalin(14), Genistein(15), Astragaluquinone(16), Formononetin (17),7-hydroxy-4′, 6-dimethoxyisoflavone(18), and Schizandrin B(19)…”
mentioning
confidence: 99%